The effectiveness of baby massage in increasing infant's body weight - Arieska, Risa; Ningrum, Kadek Agustina Puspa; Tani, Ni Luh Linda Ayuni (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Baby care that is not optimal at a critical period can cause death in the baby. The Neonatal Mortality Rate (NMR) is set to be up to 12 per 1000 live births in 2030. Massage provides a stimulus to the systems in the body, a substance that regulates functions such as appetite, sleep, memory, and learning, regulates temperature, mood, behavior, the function of blood vessels, muscle contraction, regulation of the endocrine system, and depression. Purpose: The purpose of this study is to determine the effectiveness of giving a baby massage to increase baby weight. Method: A quasi- experimental approach, specifically focusing on one group pretest - posttest. The study took place from April 2023, in Ubud Health Center, Bali. The independent variable was baby massage while the dependent variables is a baby weight. Using purposive sampling and the Slovin formula, 30 participants were selected. Univariate statistical analysis was conducted, bivariate data analysis using Shapiro-Wilk dan Wilcoxon test. Results: Shows an increase in average infant weight from 5.24 kg pre-test became to 6.19 kg after post-test and a p-value of 0.000 (<0.05), indicating that infant massage significantly affected infant weight gain. Conclusion: Proves that giving massage to babies can help optimize baby growth by increasing baby weight. Infants who are massaged have increased levels of absorption enzymes and insulin so that the absorption of food extracts becomes better.